2013
DOI: 10.1007/s00415-013-7072-2
|View full text |Cite
|
Sign up to set email alerts
|

High-rate repetitive transcranial magnetic stimulation in migraine prophylaxis: a randomized, placebo-controlled study

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is an emerging treatment for pain but there is no class 1 study on its role in migraine prophylaxis. In this study we report the efficacy and safety of high-rate rTMS in migraine prophylaxis. Adult migraine patients having >4 attacks/month were randomized to high-rate rTMS or sham stimulation. Stimulation in the form of 10 Hz rTMS, 600 pulses in 10 trains were delivered to the hot spot of the right abductor digiti minimi in 412 s. Three sessions were delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 30 publications
4
117
1
8
Order By: Relevance
“…Teepker et al showed a reduction of headache frequency in a study of low-frequency rTMS in 27 patients, but the difference was not significant compared to the sham-treated group [30]. In a randomised, double-blind, palcebo-controlled trial, 50 adult migraineurs having more than 4 attacks in a month were assigned to either high-frequency rTMS or sham treatment [31]. At 1 month, the rTMS-treated group showed a reduction in headache frequency in 78.7% compared to 33.3% in those receiving sham.…”
Section: Neurostimulation Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Teepker et al showed a reduction of headache frequency in a study of low-frequency rTMS in 27 patients, but the difference was not significant compared to the sham-treated group [30]. In a randomised, double-blind, palcebo-controlled trial, 50 adult migraineurs having more than 4 attacks in a month were assigned to either high-frequency rTMS or sham treatment [31]. At 1 month, the rTMS-treated group showed a reduction in headache frequency in 78.7% compared to 33.3% in those receiving sham.…”
Section: Neurostimulation Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Работы, посвященные использованию рТМС в лечении мигрени, немногочисленны [98][99][100][101][102][103][104][105][106]. В слепом рандомизированном плацебо-контролируемом исследовании эффективности рТМС зоны М1 левого по-лушария в лечении мигрени [105] было показано досто-верное уменьшение частоты мигренозных приступов, ин-тенсивности болей, степени инвалидизации пациентов. Клиническое улучшение связывалось с повышением уровня β-эндорфина в плазме крови.…”
Section: болевые синдромыunclassified
“…The study was approved by Institute Ethics Committee (PGI/ BE/256/2011). This is a sub analysis of our earlier study, in which we reported high rate rTMS as a migraine prophylaxis (16).…”
Section: Methodsmentioning
confidence: 99%
“…It produced a similar sound, but did not produce muscle contraction. The motor threshold, however, was not measured for sham stimulation to avoid the effect of true stimulation (16).…”
Section: High Rate Rtmsmentioning
confidence: 99%
See 1 more Smart Citation